Strategi Peningkatan Efektivitas Pembelajaran Berdiferensiasi terhadap Reversible Thinking Matematik Menggunakan Modul Digital berbasis VBA Excel Bagi Siswa SMA - Pertiwi, Citra Megiana; Putri Pratiwi, Meitia; Wardani, Adeliasari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
Adaptation in implementation and learning is the key to creating competent, excellent, and globally competitive human resources. Differentiated learning can address this challenge as it aligns with students' conditions, needs, and potential. This approach can stimulate students to master Mathematical Reversible Thinking Ability (KRTM), which plays a crucial role in students' success in solving mathematical problems. Despite its significance, field observations indicate that this ability remains relatively low. As a solution, a VBA-Excel-based digital module can be utilized in differentiated learning as a strategy to effectively enhance KRTM. he aim of this research is to assess the effectiveness of implementing differentiated learning using a VBA-Excel-based digital module to improve high school students' KRTM. The research method employed is the Mixed Method with The Explanatory Sequential Design. The research was carried out with high school students in a district in Bandung. The research instruments included ability tests and open-ended questionnaires to collect students' responses. The findings indicate that the differentiated learning strategy using a VBA-Excel-based digital module significantly improves KRTM. Students demonstrated a good understanding of the material and showed enthusiasm in learning, as the approach aligns with their characteristics and needs.